2015 Kansas Performance Tests with Soybean Varieties - Schapaugh, William T., Jr. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2017)
Soybean performance tests are conductd each year to provide information on the relative performance of new and established varieties and brands at several locations in Kansas. Main Station, Manhattan: Jane Lingenfelser, Assistant Agronomist; William T. Schapaugh, Jr., Professor (Senior Author); Brent Christenson, Research Assistant; Cheyenne Stephens, Research Assistant; Research Centers: Patrick Evans, Colby; Lonnie Mengarelli, Parsons; Monty Spangler, Garden City; Josh Coltrain, Crawford County Extension; Experiment Fields: Eric Adee, Topeka; Gary Cramer, Hutchinson; Andrew Esser, Scandia; James Kimball, Ottawa; Cooperators: Vernon Egbert, McCune; Lance Rezac, Onaga; Dale Roberds, Pittsburg; Clayton Short, Assaria.
Keywords: Soybeans; Seeds; Yields; Environmental factors; Kansas